2014
DOI: 10.1111/pde.12327
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Vitamin D–Resistant Rickets Presenting as Alopecia

Abstract: Hereditary vitamin D-resistant rickets (HVDRR) is a rare autosomal recessive disorder caused by mutations in the vitamin D receptor (VDR) gene. We report the case of an infant presenting with alopecia, growth failure, and gross motor developmental delay. Serum biochemistry and skeletal survey were consistent with rickets. After a poor response to standard treatment, genetic testing confirmed a c.147-2A>T novel mutation in the VDR gene consistent with HVDRR. It is important for dermatologists and pediatricians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…As shown in our study, various patterns of alopecia occur, ranging from total absence of hair to diffuse sparse hair, to areas of absent hair adjacent to areas with hair. There does not appear to be a correlation of the alopecia pattern with the type of mutation present [1,2,12,13] . In the present report, unrelated children with the same mutation showed different patterns of alopecia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As shown in our study, various patterns of alopecia occur, ranging from total absence of hair to diffuse sparse hair, to areas of absent hair adjacent to areas with hair. There does not appear to be a correlation of the alopecia pattern with the type of mutation present [1,2,12,13] . In the present report, unrelated children with the same mutation showed different patterns of alopecia.…”
Section: Discussionmentioning
confidence: 94%
“…Alopecia in HVDRR patients is phenotypically similar to the disease atrichia with papular lesions caused by mutations in the hairless gene ( hr ). The hr gene product HR has been shown to act as a corepressor of the VDR [1,13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…4 It may be present at birth or develop during the first year of life. 9,11,14,15,16,17,18,19,20,22 Alopecia is associated with poor prognosis and could have an important diagnostic value. 4,9,11,13,14,19,20 Histopathological examination shows hypoplastic hair follicles, follicular remnants, and cysts with no scarring or inflammation.…”
Section: Alopecia As a Sign Of Hypocalcemia Vitamin D-dependent Ricmentioning
confidence: 99%
“…2,3 Vitamin D-dependent rickets type II (VDDRII) results from the mutation on the vitamin D receptor gene (VDR), which is expressed in several target organs (intestines, kidneys, bones, parathyroid, and hair follicle). 4,5 Immunohistochemical study demonstrated the VDR expression in keratinocytes of the outer rooth sheath hair and in dermal papillae fibroblasts, with higher immunoreactivity levels during the anagen and catagen phases. Therefore, when the VDR system is not intact, inadequate differentiation of the pilous follicle takes place, separate from electrolyte homeostasis, which would explain the occurrences of these signals, specifically in VDDR type II, and which would most likely result in the maintenance of alopecia, despite the replacement of vitamin D and calcium.…”
mentioning
confidence: 98%